2014
DOI: 10.1186/preaccept-3285223921360401
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of mitogen-activated protein kinase gene family in Gossypium raimondii and the function of their corresponding orthologs in tetraploid cultivated cotton

Abstract: Background: Mitogen-activated protein kinase (MAPK) cascades play a crucial role in plant growth and development as well as biotic and abiotic stress responses. Knowledge about the MAPK gene family in cotton is limited, and systematic investigation of MAPK family proteins has not been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 50 publications
4
18
0
Order By: Relevance
“…Since the nature of protein kinase activity depends on their direct physical encounters, we conducted a comprehensive directed yeast two-hybrid (Y2H) assay to define the interactions between the last two kinases in the MAPK cascade in cotton. Besides the 28 MAPK genes reported previously 36 , we further confirmed 56, 52 and 28 MAPK genes from G. hirsutum , G. barbadense and G. arboreum , respectively ( Supplementary Dataset 2 ). Due to the high similarity (more than 97%) in the amino acid sequences ( Supplementary Table 2 ) of MKK and MAPK homoeologs in the A- and D-subgenomes, we performed PCR-based cloning for anyone of the MKK homoeologs.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Since the nature of protein kinase activity depends on their direct physical encounters, we conducted a comprehensive directed yeast two-hybrid (Y2H) assay to define the interactions between the last two kinases in the MAPK cascade in cotton. Besides the 28 MAPK genes reported previously 36 , we further confirmed 56, 52 and 28 MAPK genes from G. hirsutum , G. barbadense and G. arboreum , respectively ( Supplementary Dataset 2 ). Due to the high similarity (more than 97%) in the amino acid sequences ( Supplementary Table 2 ) of MKK and MAPK homoeologs in the A- and D-subgenomes, we performed PCR-based cloning for anyone of the MKK homoeologs.…”
Section: Resultssupporting
confidence: 84%
“…In total, eight MKK genes were cloned and sequenced to confirm their complete open reading frame (GenBank accession numbers: KX118695-KX118702) ( Table 1 ). Combined with the 21 MAPK genes cloned previously 36 , we constructed eight MKKs and 21 MAPKs into DNA binding domain and activation domain plasmid vectors, respectively. Each MKK protein was found to have a distinct auto-activation activity in yeast.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agrobacterium cultures containing recombinant TRV vectors were prepared and then infiltrated into two fully expanded cotyledons of eight-day-old seedlings, as previously described by Zhang et al . 57 . The seedlings were cultivated in a greenhouse at 23/22 °C (day/night) with a 16 h light/8 h dark photoperiod.…”
Section: Methodsmentioning
confidence: 99%
“…Little is known about the relationship between PRODH and the MAPK pathway in plants, however, hypoosmotic stress was observed to induce a similar pattern of MPK20 and PRODH expression in Arabidopsis , suggesting a link between PRODH and MPK20 ( Moustafa et al, 2008 ). A recent genomic study showed MPK20 was highly induced by H 2 O 2 stress in cotton ( Gossypium raimondii , Zhang et al, 2014 ). Is it plausible that ROS generated by proline metabolism induces MPK20 during petal senescence?…”
Section: Proline In Senescing Petals: Energy Depletion and Ros Accumumentioning
confidence: 99%